2019
DOI: 10.5171/2019.218429
|View full text |Cite
|
Sign up to set email alerts
|

White Land Tax: Evidence in the Kingdom of Saudi Arabia

Abstract: Taxes on land and property contribute to one of the revenue sources in all countries. Notably, there are countries, which do not rely on property taxation as a source of revenue such as Kingdom of Saudi Arabia (henceforth KSA). The main revenue of KSA derives from oil, which constitutes 73% of the total government's revenue. On 23 rd March 2015, the government has announced a 2.5% rate of "white land tax" under the Royal Decree M/4, dated November 2015, which may change the landscape of property market in KSA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In the KSA, there is a significant amount of unused developed land in urban areas, but a large portion of it is owned by landlords and real estate companies, who view it as an investment opportunity to be sold later at higher prices [52]. Even though the government has implemented a 'white land' program to increase the supply of developed land, its impact remains limited [38]. Similarly, in China, Taruvinga et al [14] found that the implementation of World Bank's enabling approach instruments showed that liberalization of the housing markets resulted in an increase in private-sector capital in the housing market and that the elites had captured the benefits of the enabling approach.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the KSA, there is a significant amount of unused developed land in urban areas, but a large portion of it is owned by landlords and real estate companies, who view it as an investment opportunity to be sold later at higher prices [52]. Even though the government has implemented a 'white land' program to increase the supply of developed land, its impact remains limited [38]. Similarly, in China, Taruvinga et al [14] found that the implementation of World Bank's enabling approach instruments showed that liberalization of the housing markets resulted in an increase in private-sector capital in the housing market and that the elites had captured the benefits of the enabling approach.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding property taxation, the government has launched the White Land program, which applies fees to residential vacant land to increase the supply of residential land to the housing market [38]. In 2015, a 2.5% rate of 'white land tax' was implemented under the Royal Decree M/4, dated November 2015, which seeks to change the landscape of the property market in the country.…”
Section: Developing Property Rightsmentioning
confidence: 99%
See 2 more Smart Citations
“…The alternative enforcement approach of imposing an idle land tax should be taken into consideration to urge landowners to develop their idle land. Referring to other countries, the tax imposition approach to these idle lands is implemented, such as in Saudi Arabia (Zakaria et al, 2019), Philippines (Lebrilla, 2016), Thailand (Medina, 2020;Fung and Mcauley, 2020a), Grenada (Godfrey, 2014), Cuba (Castro Morales, 2018; González and Alfonso, 2018), India (CWAS, 2020), Cambodia (IPS Cambodia, 2019;Fung and Mcauley, 2020b), South Africa (Mosha, 2010) and Japan (Japan Property Central, 2019).…”
Section: Research Backgroundmentioning
confidence: 99%